Tris(2, 2′‐bipyridine)iron(II) bis(1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide) dihydrate: chiral hydrogen‐bonded frameworks interpenetrate in three dimensions. Issue 5 (23rd April 2014) - Setifi, Zouaoui; Setifi, Fatima; Boughzala, Habib; Beghidja, Adel; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title compound, [Fe(C10H8N2)3](C9H5N4O)2·2H2O, the chiral cations lie across twofold rotation axes in the space group C2/c. The anions and the water molecules are linked by two independent O—H...N hydrogen bonds to form C22(8) chains, and these chains are linked by the cations via C—H...N and C—H...O hydrogen bonds to form two interpenetrating three‐dimensional frameworks, each of which contains only one enantiomeric form of the chiral cation.